Characteristics and implications of a diversified circular economy: the case of a Belgian not-for-profit cooperative - Emmery, Irma; Paredis, Erik (Frontiers in Sustainability, 2025)
IntroductionThe circular economy as a resource sustainability strategy is both established and contentious in and beyond academia. This paper contributes to the growth-critical scholarship on circularity, starting from the premise that circular economic diversity is both a function of, and is required for, an economy beyond growth-dependencies. Exploring the question what this diverse circularity might look like on the ground, our paper inventories the wide range of circular activities and relationships taking place in a not-for-profit maker cooperative in Belgium and studies their main characteristics.MethodologyWe deploy the diverse economies (DE) framework, which presents us with theoretical concepts and qualitative-ethnographic methods (long-term observation, participation, depth interviews) that enable the study and classification of economic activity. It is designed to broaden the scope of the ‘circular economic’ by including non-market and informal practices.ResultsWe found that many of the circular activities we observed (repairing, urban mining, reusing, dismantling, maintaining) are often overlooked in the literature on CE strategies, tend to involve a wider variety of materials than in the for-profit CE (unruly left-over materials, outdated furniture, bicycle components typically discarded), and occur within a wider range of economic dynamics (including informal and non-monetary encounters). We also identified four characteristics that pattern these diverse activities and relations: diversified material value and purpose, redefined work, social embeddedness, and resilience in the face of precarity.DiscussionBased on these results, we make the case that a diversified circular economy might be crucial for our collective wellbeing in critical futures: it includes more diverse actors, is more materially creative, includes a wider skill-set and is more tethered to local community approaches to provisioning. Lastly, the paper highlights why and how structural barriers related to spatial planning and financial investment need to be overcome in order to support diverse circularities.